A computational simulation of foreshore wave at rocky coast landform near Terengganu coastline during monsoon season / Muhammad Luqman Hakim Mohd Shaiful Afzam - Mohd Shaiful Afzam, Muhammad Luqman Hakim (2022)
There is no record or studies on foreshore wave Terengganu coastline landform during monsoon season especially rocky beach, so it hard to predict how the wave at that beach flow. By using Ansys Space Claim, the model of Pantai Teluk Bidara had been designed. The wave also has been simulated by using Ansys Fluent to know how the wave flow at that beach. As the result, we can see how the wave at the foreshore at rocky beach will flow. From this, the simulation will enhance understanding how wave at foreshore of rocky beach at Terengganu during monsoon season flow. This helps the enhance community understanding how the wave flow.